Introduction to statistics fundamental concepts and procedures of data analysis - Reid, Howard M. (Sage Publications, Inc., 2014)
Keeping computational challenges to a minimum, the author shows readers how to conduct a variety of commonly used statistical procedures as well as when each procedure should be utilized.